The re-do list - Williams, Denise, 1982- (Berkley Romance, 2026)
"What would you do with a second chance at your first time? Following a bad breakup, Willow Lewis tackles a re-do list with the help of her brother's best friend in this sweet and sexy new romance from USA Today bestselling author Denise Williams. Willow experienced all her big firsts with her high school sweetheart. Now, reeling from their very public breakup, she wants to get a re-do on those important moments. While dog-sitting for her brother during his deployment, she has a chance to start over and spending time with his best friend gives her the confidence to start checking items off her "Re-Do list." Deacon promised his best friend two things when Cruz left for a deployment: that he'd look out for Willow, and that he'd keep his hands off Cruz's baby sister. "Operation Re-Do" is innocent enough at first: Deacon likes Willow and he's willing to help her out any way he can. But when the list of firsts turns from a first dance to first kisses and more, Deacon can't deny the connection he feels to Willow. As Deacon's and Willow's firsts turn to seconds, thirds, and fourths, this pair can't get enough of each other-and they support each other through new challenges. But they are both aware there's an end date to Willow's time in town... and even if she were to stay, Deacon doesn't know how to choose between his loyalty to his closest friend and the woman he's fallen in love with. With no more romantic moments on her list for them to re-do, can these two still find a way to stay together?"-- Provided by publisher.